Living myocardial slices: Advancing arrhythmia research - Amesz, Jorik H.; Zhang, Lu; Everts, Bian R.; De Groot, Natasja M. S.; Taverne, Yannick J. H. J. (Frontiers in Physiology, 2023)
Living myocardial slices (LMS) are ultrathin (150 – 400 µm) sections of intact myocardium that can be used as a comprehensive model for cardiac arrhythmia research. The recent introduction of biomimetic electromechanical cultivation chambers enables long-term cultivation and easy control of LMS culture conditions. The aim of this review is to present the potential of this biomimetic interface using LMS in electrophysiological studies outlining advantages, disadvantages and future perspectives of the model. Furthermore, different electrophysiological techniques and their application on LMS will be discussed. The developments of LMS in electrophysiology research will hopefully lead to future breakthroughs in the understanding of cardiac arrhythmia mechanisms and the development of novel therapeutic options.